Assessing the Reality of Strategic Planning in the General Tobacco Corporation "Exploratory Study" - دالي, مجد جهاد; تركمان, حنان; ماخوس, ديمة (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the research is to assess the reality of strategic planning through its dimensions: vision, mission, strategic objectives, strategic analysis, strategic choice, strategy implementation, evaluation and control, through a survey of the opinions of stakeholders in the General Tobacco Corporation. The researcher relied on the descriptive approach, and the study population included all officials from managers, assistants, heads of departments and assistants, in addition to workers responsible for production, planning, marketing and quality operations in the General Tobacco Corporation (the General Administration in Latakia Governorate, and the coastal region branch), where their number reached (329). Individuals distributed among (106) individuals in the public administration, and (223) individuals in the coastal region branch. Accordingly, and using the comprehensive inventory method, the researcher distributed (329) questionnaires, (315) complete and valid questionnaires were retrieved for statistical analysis, distributed between (106) questionnaires in the public administration, and (223) questionnaires in the coastal area branch, with a response rate It reached (95.74%). The results showed that the reality of strategic planning with its dimensions (vision, mission, strategic objectives, strategic analysis, strategic choice, strategy implementation, evaluation and control) in the institution under study is a good reality, with relative importance (75.2%).